2021
DOI: 10.1111/jpy.13140
|View full text |Cite
|
Sign up to set email alerts
|

Thallus Growth Stage and Geographic Origin Shape Microalgal Diversity in Ramalina farinacea Lichen Holobionts

Abstract: Lichen symbioses are microecosystems hosting many other living organisms besides the two major lichen symbionts (i.e., lichenized fungi [the mycobiont] and green microalgae or cyanobacteria [the photobiont]). Recent investigations evidenced that other fungi, non‐photosynthetic bacteria, and microalgae co‐inhabit within the lichen thalli, but their diversity and their roles are still underinvestigated. Here we present an ad hoc stratified sampling design and in‐depth Illumina paired‐end metabarcoding approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 79 publications
(193 reference statements)
8
37
0
Order By: Relevance
“…Thallus tips were the only zones free of epiphytes in all samples. The choice of thallus tips is also supported by the finding of Molins et al (2021) , who reported that there were no differences in photobiont composition among different parts of the thallus in specimens of a species of the same genus ( R. farinacea ) from the same biogeographic region as the present study. Samples were washed with acetone to remove secondary metabolites and stored at −80°C.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Thallus tips were the only zones free of epiphytes in all samples. The choice of thallus tips is also supported by the finding of Molins et al (2021) , who reported that there were no differences in photobiont composition among different parts of the thallus in specimens of a species of the same genus ( R. farinacea ) from the same biogeographic region as the present study. Samples were washed with acetone to remove secondary metabolites and stored at −80°C.…”
Section: Methodssupporting
confidence: 88%
“…TR9 as main photobiont is not exclusive of the R. decipiens group. It was found in Macaronesian specimens of R. farinacea using Sanger sequencing ( del Campo et al, 2013 ) and NGS ( Molins et al, 2021 ). BLAST searches of the two predominant ASVs revealed their presence also in other genera.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies (Chiva 2020;Molins et al 2020;Moya et al 2020), the ultrastructure of symbiotic microalgae observed in lichen fragment of both thalli (MT27 and TE1) fits with typical features of the genus Trebouxia (Appendix S4 in the Supporting Information). In studies carried out on the diversity of microalgae in lichen thalli by massive sequencing (454, Illumina), several genera of green microalgae were always detected (Moya et al 2017;Molins et al 2021), although in a low proportion and, in general, their sequences are not usually available in GenBank. Moreover, no microalgae have been identified with the genetic and morphological characteristics of the genus Watanabea.…”
Section: Watanabea Spp Lifestylesmentioning
confidence: 99%
“…Lichen thalli are complex symbiotic micro-ecosystems where an exhabitant fungus (mycobiont) interacts with extracellular lineages of microalgae (phycobionts/photobionts). Additionally, non-photosynthetic bacteria, other fungi and diverse green microalgae also participate in the symbiosis, self-maintaining the viability of the thalli (holobionts) (Aschenbrenner et al 2016;Smith et al 2020;Molins et al 2021). The symbiogenetic phenotypes resulting from mutualistic interactions within microbial assemblages provide a survival strategy to thrive under extreme conditions, for example in polar areas and xeric deserts (Barreno 2013;Raggio et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation